2020
DOI: 10.3389/fnagi.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by the Immunomodulatory Drug Pomalidomide in the Drosophila LRRK2WD40 Genetic Model of Parkinson’s Disease

Abstract: Immunomodulation in Parkinson's Disease immunomodulatory agent POM in a genetic model of PD. POM is an FDA-approved clinically available and well-tolerated drug used for the treatment of multiple myeloma. If further validated in mammalian models of PD, POM could rapidly be clinically tested in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 87 publications
(113 reference statements)
1
19
0
Order By: Relevance
“…Pomalidomide has been investigated for use in neurological conditions such as Parkinson’s disease. It can improve age-related neurological impairment/motor disability 76 and can reduce ischemic brain injury in an in vivo study 77 .…”
Section: Resultsmentioning
confidence: 99%
“…Pomalidomide has been investigated for use in neurological conditions such as Parkinson’s disease. It can improve age-related neurological impairment/motor disability 76 and can reduce ischemic brain injury in an in vivo study 77 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, thalidomide remains a treatment choice for erythema nodosum leprosum (ENL), an inflammatory complication of leprosy, which was first described in Sheskin (1965) and FDA approved in 1998 ( Melchert and List, 2007 ; Asatsuma-Okumura et al, 2020 ). Preclinical studies of FDA approved IMiDs, as well as novel IMiDs such as 3,6′-dithiopomalidomide (3,6′-DP) and adamantyl thalidomide derivatives, support repurposing of IMiDs as therapeutics for neurological diseases with inflammatory components, such as AD, PD, stroke, traumatic brain injury and multiple sclerosis ( Russo et al, 2012 ; He et al, 2013 ; Yoon et al, 2013 ; Eitan et al, 2015 ; Wang et al, 2016 ; Boi et al, 2019 ; Casu et al, 2020 ; Lin et al, 2020 ; Hsueh et al, 2021 ; Figure 2 ). Compared with classical immunosuppressants and TNF-α-targeting drugs such as Etanercept and Infliximab, the pharmacokinetic features of IMiDs offer several advantages that make them more suitable for treating chronic neurological disorders.…”
Section: Immunomodulatory Imide Drugs (Imids)mentioning
confidence: 99%
“…Interestingly, IMiDs decreased the α-Syn-induced inflammatory response also in non-motor regions of the brain such as the hippocampus, an area involved in cognitive deficits of PD, supporting a role of neuroinflammation in these non-motor symptoms ( Valera et al, 2015 ; Williams-Gray et al, 2016 ). A recent study demonstrated the pomalidomide efficacy in a drosophila LRRK2 WD40 mutant PD model, with LRRK2 being a common genetic cause of PD ( Casu et al, 2020 ; Dues and Moore, 2020 ). These flies develop motor impairment and gradually lose dopaminergic neurons with age ( Casu et al, 2020 ).…”
Section: Imids and Neurodegenerative Disorders: Preclinical And Clinical Evidencementioning
confidence: 99%
See 2 more Smart Citations